Pengaruh Kesejahteraan Pegawai, Motivasi Intrinsik, Dan Beban Kerja Terhadap Produktivitas Pegawai Pada Balai Pelestarian Kebudayaan Wilayah XX Maluku - Wakim, Mezak; Ohoiwutun, Stanislaus Kostka; Selanno, Hendry (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of Employee Welfare, Intrinsic Motivation, and Workload on Employee Productivity at the Cultural Heritage Preservation Center Region XX in Maluku. A quantitative approach was used with multiple linear regression analysis. Data were collected through questionnaires distributed to 93 respondents who are active employees at the institution. The results indicate that partially, Employee Welfare and Intrinsic Motivation have a significant effect on Employee Productivity, while Workload does not show a significant effect. Intrinsic Motivation yielded the highest regression coefficient, indicating it is the most dominant factor in improving productivity. Simultaneously, the three independent variables significantly influence Employee Productivity, with a coefficient of determination (R²) of 0.917. This means that 91.7% of the variation in productivity can be explained by welfare, intrinsic motivation, and workload. These findings highlight the importance of enhancing welfare and empowering intrinsic motivation as core strategies for improving employee performance. The study provides both theoretical and practical contributions to human resource management in the public sector, especially in developing performance-based policies.